Association of hyperchloremia with acute kidney injury in children with major trauma (Annals of Medical Research, 2023)
Aim: Hyperchloremia is related to the risks of several morbidities and mortality in seriously sick cases. The effect of hyperchloremia on the incidence of acute kidney injury (AKI) in trauma patients is not well known.  Association of hyperchloremia and AKI within the first 72 hour of pediatric intensive care unit (PICU) admission in pediatric trauma patients was investigated.Materials and Methods: A total of 137 patients with major trauma were investigated retrospectively from tertiary hospital. Serum chloride levels ≥ 110 mmol/L described as hyperchloremia. Clinical and laboratory data were compared between AKI and non-AKI. A multivariate logistic regression analysis was used to determine the association between hyperchloremia and AKI.Results: Totally 109 children were favorable for evaluation following the application of suitability criteria. On admission and at 72 hours, electrolyte measurements were similar between two groups, however chloride level was significantly higher in AKI group (112.33 ± 4.74 vs. 109.07 ± 4.90 mmol/L; p< 0.01) at 72 hours. Ratio of hyperchloremia was remarkably more common in AKI group (p
Keywords: Acute kidney injury; Hyperchloremia; Major trauma pediatric